On the usefulness of Nietzsche to strengthening the critical radicality of Critical Management Studies - Norbert Lebrument (Cogent Business & Management, 2024)
AbstractIt is well known that there is little interest in Nietzschean thought in the management sciences. This observation is supported by the low number of articles published in management science journals that use what could be called the Nietzschean conceptual framework or even part of it. This observation of a weak mobilization of the Nietzschean corpus can be explained, on the one hand, by the non-univocal character of the Nietzschean style and, on the other hand, by the critical radicality of Nietzschean thought. Given this situation, one might expect Critical Management Studies to make significant use of Nietzschean concepts, especially Nietzschean genealogy. But this is not the case. Nietzsche’s work is hardly used by Critical Management Studies (CMS). Yet CMS, because it seeks to question and challenge existing managerial practices by analysing the power dynamics, processes of domination and inequalities that are expressed in organisations, could benefit from the Nietzschean genealogy. Indeed, Nietzschean genealogy, which aims to shed light on the history and origins of values, can provide useful insights into the critical work carried out by CMS and broaden their scope of investigation. In this essay, I argue that CMS should incorporate Nietzschean genealogy into their research in order to strengthen the critical scope of their work when questioning the axiological foundations of managerial practices and exploring the power relations that run through organisations.